2017
DOI: 10.1007/s00330-017-4769-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient radiation doses and reference levels in pediatric interventional radiology

Abstract: • We determined reference levels (RLs) for bAVM embolization, DSA and SVM sclerotherapy. • The proposed RLs will permit benchmarking practice with an external standard. • The proposed RLs by age may help to develop paediatric dose guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In order to protect the population beyond the acute phase, it is critical to seek for any method that might reduce thrombectomy patients' X-ray exposure. There are currently no established dose reference levels for a thrombectomy procedure that could help measure and improve the treatment quality of ionizing examinations [13] despite recent publications [14,15] as already established for many image-guided diagnostic and interventional procedures [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In order to protect the population beyond the acute phase, it is critical to seek for any method that might reduce thrombectomy patients' X-ray exposure. There are currently no established dose reference levels for a thrombectomy procedure that could help measure and improve the treatment quality of ionizing examinations [13] despite recent publications [14,15] as already established for many image-guided diagnostic and interventional procedures [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…29 Less is known about the radiation dose for pediatric DSA; however, in one study, the reported DAP range for cerebral DSA in children younger than 18 years was 3.8 to 23.2 Gy×cm 2 . 11 The mean DAP was higher in our study because some of the analyzed digital subtraction angiograms were obtained for a combination of diagnostic and treatment purposes. Our findings, therefore, suggest a potential role of fe-SPGR in the diagnostic evaluation of AVMs, which is important in the pediatric population given the risk of radiation exposure with CTA and DSA, especially when considering that most of these patients often undergo repeat surveillance imaging.…”
Section: Discussionmentioning
confidence: 71%
“…For pediatric non-cardiologic interventional procedures, data is even scarcer. There is only one multicenter study from France publishing reference levels of three interventional neuroradiological procedures (cerebral digital subtraction angiography (DSA), embolization of brain arteriovenous malformation (bAVM), and percutaneous sclerotherapy of head and neck superficial vascular malformation (SVM)) [36]. Authors differentiated patient collective to different age groups: younger than 2 years (A1), aged 2-7 years (A5), 8-12 years (A10), and 13-18 years (A15).…”
Section: Discussionmentioning
confidence: 99%
“…For IR procedures, the patient dose depends on several factors, including the age and size of the patient, the complexity of the specific situation, and the experience of the medical staff. In general, therapeutic procedures have been reported to yield higher dose than diagnostic procedures [36]. Therefore, pediatric DRLs should be defined separately for specified diagnostic or therapeutic procedures [5].…”
Section: Discussionmentioning
confidence: 99%